Handling Children's Speech Delay Through Fables Using Finger Puppets - Sisi Rosida; Ristra Sandra Ritonga; Rizky Vita Losi (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
Overcoming speech delays are the most frequently complained about by parents. Delays in speaking for children will have an impact on their learning process at school, including: difficulties in reading, writing and adapting. The aim of this study was to find out the process of fables through finger puppets as an effort to deal with children's speech delays. Role playing using finger puppets is an alternative in handling children's speech delays. The method used is field research which is descriptive qualitative in nature, located in the Kelompok Belajar IT Alwashliyah. The research subjects included 14 students and class teachers. Data collection was obtained through observation, interviews, and documentation. The results of the study found, (1) Symptoms of children who experience speech delays, such as: difficulty speaking, speech disorders which include searching vocabulary lists in memory (finding words), difficulty identifying elements in a story, difficulty in building sentences, the vocabulary is unclear, and the child doesn't want to talk at all. (2) Efforts made in dealing with children who are late in speaking have had a direct impact on children, providing affection with animal roles to foster self-confidence, creating direct interaction between children and teachers to establish stimulating communication in children. (3) The fable method uses finger puppets which affect children's language development, one of which is speech delay caused by a lack of language stimulus. Gradually, children who experience speech delays begin to open up and want to interpret words even though they are still stammering.